Penentuan Sistem Pendukung Keputusan Dalam Kinerja Pegawai Menggunakan Metode SAW - Muhammad Nurwafi (Jurnal Ilmu Komputer dan Sistem Informasi, 2022)
The performance of employees who get bonuses is one of the conditions used for companies to support employee performance, evaluate work results, and motivate other employees to work hard. In addition to assessing the work of employees according to company standards, job evaluation in an organization or company is usually used as a benchmark for companies to issue bonuses to employees. The problem in this study is that excessive workloads on some employees result in stress which leads to poor performance. This research process uses aadecision supporttsystem toodetermineeand select the performance of employees who get bonuses, the SPK process through the criteria and weights used are attendance (25%), attitude/ethics (20%), time discipline (25%), creativity (15%), %), and work results (15%). This study aims to determine the performance of employees who are rewarded using the direct weighting (SAW) method for an employee performance decision support system. In this study, the data collection technique used was library research, observation. A decision support system to evaluate the performance of employees who have been rewarded.